Efficiency of Health Investment: Education or Intelligence? - Govert Bijwaard; Hans van Kippersluis (Tinbergen Institute, 2014)
In this paper we hypothesize that education is associated with a higher efficiency of health investment, yet that this efficiency advantage is solely driven by intelligence. We operationalize efficiency of health investment as the probability of dying conditional on a certain hospital diagnosis, and estimate a multistate structural equation model with three states: (i) healthy, (ii) ill (in hospital), and (iii) death. We use data from a Dutch cohort born around 1940 that links intelligence tests at age 12 to later-life hospitalization and mortality records. The results suggest that higher Intelligence induces the higher educated to be more efficient users of health investment - intelligent individuals have a clear survival advantage for most hospital diagnoses - yet for unanticipated health shocks and diseases that require complex treatments such as COPD, education still plays a role.
Keywords: C41; I14; I24; 330; Education; Intelligence; Health; Multistate duration model